Centering "Grace": Challenging Anti-Blackness in Schooling Through Motherwork. Issue 1 (January 2021) - Watson, Terri N.; Baxley, Gwendolyn S.
Anti-Blackness is global and present in every facet of society, including education. In this article, we examine the challenges Black girls encounter in schools throughout the United States. Guided by select research centered on Black women in their roles as mothers, activists and school leaders, we assert that sociologist Patricia Hill Collins'concept of Motherwork should be an essential component in reframing the praxis of school leadership and in helping school leaders to rethink policies, practices, and ideologies that are anti-Black and antithetical to Blackness and Black girlhood. While most research aimed to improve the schooling experiences of Black children focuses on teacher and school leader (mis)perceptions and systemic racial biases, few studies build on the care and efficacy personified by Black women school leaders. We argue that the educational advocacy of Black women on behalf of Black children is vital to culturally responsive school leadership that combats anti-Blackness and honors Black girlhood. We conclude with implications for school leaders and those concerned with the educational experiences of Black children, namely Black girls.